ANALISIS PENERAPAN DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN - Wa Ode Nur Asysyifaa; Juharsah; Isalman; Asrip Putera; Triwulandari Nehru Putri; Windayani (Jurusan Manajemen FEB UHO, 2024)
This study aims to determine how the application of digital marketing in increasing sales. This study uses a qualitative research type. The informants in this study are shop owners and employees as key informants and one customer as a supporting informant. This research method uses three data collection techniques, namely, interviews, observations, and literature studies. The study was conducted at the Kendari Arshop store. The results of the study show that the Kendari Arshop store is very consistent in using digital marketing. So that it facilitates interactivity, informativeness, personalization, and trends. These conveniences continue to the accuracy of selling price determination, increasing cost efficiency, demand and sales.